Preliminary results of the application of Transient Electromagnetic Method in the area of Karla lake (East Thessaly basin, Greece) - Alexopoulos, J.D.; Dilalos, S.; Mitsika, G.S. (11th International Hydrogeological Congress, 2017)
In this paper we discuss the preliminary results of the Transient Electromagnetic Method (TEM) that was applied in the area of Karla Lake, located in the East Thessaly basin. A grid of 71 TEM soundings was planned and executed in order to investigate the subsurface lithological and hydrogeological conditions of the area. The geological regime of the area is comprised of the alpine basement (marbles, gneisses and schists), ophiolites, transgression formations and finally a package of post-alpine deposits with respectful thickness. Resistivity maps for certain depths of investigation along with a pseudo-3D representation were produced, based on the processed TEM data. The vertical distribution of the resistivity values revealed important information about the lithological succession of the area and the hydrogeological status of the post-alpine sediments covering the basin. Moreover, the limits of the former Karla Lake were delineated and the alpine bedrock was also adumbrated under the thick Tertiary and Quaternary deposits. Finally, taking into account older piezometric maps of 2009 and our geophysical results, we managed to indicate the decline of the groundwater level since then, in the central part of the study area and the broader area of Kileler settlement.